2004
DOI: 10.1021/jp047736t
|View full text |Cite
|
Sign up to set email alerts
|

Hole Scavenging and Photo-Stimulated Recombination of Electron−Hole Pairs in Aqueous TiO2 Nanoparticles

Abstract: It is shown that 532 nm and 1064 nm laser photoexcitation of trapped electrons generated by 355 nm photolysis of aqueous titania (TiO 2 ) nanoparticles causes rapid photobleaching of their absorbance band in the visible and near IR. This photobleaching occurs within the duration of the laser pulse (3 ns FWHM); it is caused by photoinduced electron detrapping followed by rapid recombination of the resulting free electron and a trapped hole. The quantum yield for the electron photobleaching is ca. 0.28 for 532 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
125
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(140 citation statements)
references
References 55 publications
(380 reference statements)
14
125
1
Order By: Relevance
“…The well dispersion of TiO2 nanoparticles was attributed to the strong interaction between PVA and TiO2. The large amount of hydroxyl groups on PVA chains acted as anchoring sites for TiO2 nanoparticles via the formation of octahedral complex or other chelating ligands with under-coordinated Ti atoms on TiO2 surfaces [31]. Attenuated total reflectance FTIR (ATR-FTIR) spectroscopic measurement was used to investigate the formation of surface complex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The well dispersion of TiO2 nanoparticles was attributed to the strong interaction between PVA and TiO2. The large amount of hydroxyl groups on PVA chains acted as anchoring sites for TiO2 nanoparticles via the formation of octahedral complex or other chelating ligands with under-coordinated Ti atoms on TiO2 surfaces [31]. Attenuated total reflectance FTIR (ATR-FTIR) spectroscopic measurement was used to investigate the formation of surface complex.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, addition of holes scavengers can greatly improve the photocatalytic reduction rate of Cr(VI) [25]. It has been reported that polyhydroxylated compounds, such as glycerol, sugar, and PVA, are highly efficient hole scavengers for TiO2 nanoparticles [31]. 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) spin-trapping EPR technique was employed to determine the species generated during photocatalytic reduction process.…”
Section: Mechanism Of Photocatalytic Reduction Of Cr(vi) Over Pva/tiomentioning
confidence: 99%
“…They also serve as active sites for the adsorption of reactants and intermediates [201]. It was concluded by time-resolved transient absorption spectroscopy [202,203] that C2-C6 polyols and carbohydrates could scavenge 50-60% of the photogenerated holes of TiO 2 in the time lapse of 6 ns. The scavenging efficiency was higher for increasing the number of OH groups.…”
Section: Photoreforming Of Alcoholsmentioning
confidence: 99%
“…From the viewpoint of utilizing solar light, visible light responsive TiO 2 -based photocatalysts are highly desired [9][10][11][12]. Moreover, TiO 2 has a relatively high electron-hole recombination rate, which will decrease its photoactivity [13][14][15].…”
Section: Introductionmentioning
confidence: 99%